Carbon Nanotube Sponges, Aerogels, and Hierarchical Composites: Synthesis, Properties, and Energy Applications. Issue 17 (14th June 2016) - Lin, Zhiqiang; Zeng, Zhiping; Gui, Xuchun; Tang, Zikang; Zou, Mingchu; Cao, Anyuan
Abstract : Carbon nanotube (CNT) aerogels and sponges are macroscopic porous materials with a unique isotropic structure. CNTs make an interconnected 3D scaffold, therefore the resulting aerogels are robust, highly conductive, and flexible, enabling a much broader range of applications than aligned arrays and thin films, especially in energy and environmental areas. A comprehensive overview of the recent progress in isotropic CNT‐based macroscopic structures is provided, including their synthesis methods, structural characteristics, mechanical properties, and deformation mechanism, as well as potential applications in energy and environmental fields. In particular, this study focuses on the CNT sponges developed, which are high‐performance porous materials with many distinct properties such as their versatile deformations and shape recovery. Importantly, the CNT sponges provide a universal platform for designing and manufacturing a variety of hierarchical functional composites by introducing polymers or inorganic guests, thus greatly extend application areas from highly compressible electrodes for supercapacitors and batteries, catalysis, to environmental cleanup. Future research directions and associated challenges in this field are proposed. Abstract : Carbon nanotube (CNT) sponges and aerogels represent emerging highly porous, isotropic structures combining outstanding mechanical and electrical properties. Recent progresses of macroscopic CNT‐based sponges, aerogels, and hierarchical composites, including their synthesis methods, structural characteristics, mechanical properties, as well as potential applications in energy and environmental fields, are summarized. Future research directions and associated challenges in this field are proposed.